Evaluation of Efficient Line Lengths for Better Readability - Zahid Hussain; Syed Asif Ali Shah; Wajiha Shah (Mehran University Research Journal of Engineering and Technology, 2012)
In this paper the major findings of a formal experiment about onscreen text line lengths are presented. The experiment examined the effects of four different line lengths on the reading speed and the reading efficiency. Efficiency is defined as a combination of reading speed and accuracy. Sixteen people between the age of 24 and 36 participated at the experiment. The subjects had to read four different texts with an average line length around 2000 characters. The texts contained substitution words, which had to be detected by the subjects to measure reading accuracy. Besides objective measures like reading speed and accuracy, the subjects were asked to subjectively vote on their reading experience. The results from our objective measures show strong similarities to those of the work done previously by different researchers. The absolute reading speed grows when the line length grows from CPL (Characters Per Line) 30-120. The measured reading efficiency, however, doesn\\\'t grow steadily, although a growing trend can be seen. This is due to the fact, that the test persons found in average more substitution words from the 60 CPL text than they did from the 30 and 90 CPL texts. The reading speed seems to increase while the line length increases but the overall comprehension seems to peak at medium line lengths. As in the previous studies, our test persons also prefer the medium (60 and 90 CPL) line lengths, although they perform better when reading longer lines. In the overall subjective opinion 13 out of 16 test persons selected the 60 or 90 CPL line length as their favorite. The literature doesn\\\'t truly provide a scientific explanation for the difference between the objective performance and the subjective preference. A natural hypothesis would be that the line length that is the fastest to read would also feel most comfortable to the readers but in the light of this and the earlier research it seems like this is not the case.